After modernity . . . what? agenda for theology - Oden, Thomas Clark, 1931- (Grand Rapids, MI Zondervan, 1990)
Includes bibliographical references and index.
Keywords: Theology -- 20th century; Postmodernism -- religious aspects -- Christianity; Liberalism (Religion) -- protestantism -- controversial literature